STRUCTURAL INJUNCTIONS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Faced with a context of judicial activism, we intend to draw attention to the importance of adequate procedural technique for processing demands related to social public policies. In the current context, mass litigation has been dealt with via pseudo-individual actions or collective actions, thought within a dual patrimonial logic. With this work, we intend to analyze the structural process as a proper way for the dialogical and cooperative construction of complex dispute solutions. This is a paradigm shift, in which the traditional, retrospective and static process is abandoned, to use a systemic, prospective and dynamic process, in which judging goes from the subsumption of the law to the concrete case for the diagnosis, planning, implementation and evaluation, in a cyclical movement of joint construction of efficient responses to the greater realization of fundamental rights.